Pengaruh Keselamatan Dan Kesehatan Kerja (K3) Terhadap Kinerja Karyawan Pada Masa Pandemi Covid-19 Pada Pt Bank Syariah Mandiri Cabang Padang - Siska Khairani; Prima Yulianti (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
The company will run well and smoothly if it is supported by various potential sources such as human resources (employees or employees), adequate company infrastructure, wages or salaries, and work locations. Employees play an important role in a company organization, so that efforts are needed to process them in order to achieve a balance in order to achieve company goals. Employees are one of the groups that are at risk of contracting Covid-19, therefore there is a need for special handling of employees regarding occupational safety and health (K3) which will affect employee performance. This study aims to determine the effect of occupational safety and health on employee performance during the Covid-19 pandemic (a case study at PT. Bank Syariah Mandiri, Padang Branch). The sample in this study were 80 employees of Bank Syariah Mandiri Branch Padang. The sampling technique used the total sampling method or the census method. The data analysis used was Statistical Product and Service Solutions (SPSS). The results obtained in this study are work safety and occupational health simultaneously have a positive and significant effect on employee performance